(3ehGgH GdbOjQ Ydi GdLGeY GdUZjQs - (3GdCHjGQj, aGjO Hf eHGQc, (B1063 (3g`s
(3ChdgG (B:s
(3HYO GdHSedI hGdJUdjI (B: (3MQa GdNGA GdeYLeI Cj gPG HGH GdCMGOjK GdeHOhAI HgPG GdMQa bGd GdfHj Udi Gddg Ydjg hSde (B: " (3NGH YHO hNSQ (B( (3Cj MQe hgdc (B) (3de jLYd Gddg JYGd aj bdHg QMeI ddHTQ (B" (3dCf Gdg QMje hjMH ef YHGOg GdQMeI s
(3BNQgG (B:s
(3aLYd ddfUGQi dJaQOge Yf ehGWf GdNjQGJ hGdSYGOGJ hcGf cd eG NUJ Hg cd CeI ef GdCjGe OdjdG Ydi CMhGdgG heG jDhd CeQgG Edjg (B( (3J(B) (3aj GdJaSjQ (B( (3gb (B) (3Yf CHj gQjQI QVj Gddg Yfg hbO Je GdcdGe Ydi Md CdaGX gPg GdGMGOjK GdfHhjIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B5 / 125s
(3eYLe GdeDdajf (B2 / 609s
(3EjVGM Gdecfhf (B2 / 602s
(3gOjI GdYGQajf (B1 / 814s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdMOjK hGdeUWdMs